Teorema de descomposición de módulos sobre dominios de ideales principales (2020)
In this work an introductory study of module theory is made. A module is a structure defined analogously to a vectorial space but replacing the field by a ring. First, we provide some definitions, notations, and key necessary results which are going to help us with the understanding of the structure of finite generated modules (F.G.M) over a principal ideal domain (P.I.D). The focus of this project is the study of module theory, principally by using tools like ring theory and group theory. Finally, an application of the module decomposition theorem over P.I.D. to the Jordan and rational normal forms is presented, i.e. we are going to establish a connection between an important theorem of module theory and some linear algebra structures.